Phases of match-play in professional Australian Football: Distribution of physical and technical performance. Issue 14 (17th July 2020) - Rennie, Michael J.; Kelly, Stephen J.; Bush, Stephen; Spurrs, Robert W.; Austin, Damien J.; Watsford, Mark L.
ABSTRACT: The current study aimed to describe the distribution of physical and technical performance during the different phases of play in professional Australian Football. The phases of play (offence, defence, contested play, umpire stoppages, set shots and goal resets) were manually coded from video footage for a single team competing in 18 matches in the Australian Football League. Measures of physical performance including total distance (m), average speed (m · min −1 ), low-speed running (LSR, <14.4 km h −1 ), high-speed running (HSR, >14.4 km h −1 ), accelerations (2.78 m · s −2 ) and decelerations (−2.78 m · s −2 ) were derived from each phase of play via global positioning system (GPS) devices. Technical skill data including tackles, handballs and kicks were obtained from a commercial statistics provider and derived from each phase of play. Linear mixed-effects models and effect sizes were used to assess and reflect the differences in physical and technical performance between the six phases of play. Activity and recovery cycles, defined as periods where the ball was in or out of play were also described using mean and 95% confidence intervals. The analysis showed that several similarities existed between offence and defence for physical performance metrics. Contested play involved the highest total distance, LSR, accelerations, decelerations and tackles compared to all other phases. Offence and defence involved the highest average speed and HSR running distances. Handballs and kicks were highest during offence, while tackles were highest during contested play, followed by defence. Activity and recovery cycles involved mean durations of ~110 and ~39 s and average speeds of ~160 and ~84 m · min −1, respectively. The integration of video, GPS and technical skill data can be used to investigate specific phases of Australian Football match-play and subsequently guide match analysis and training design.